Making sense of domestic wildlife and CITES legislation: The example of Nepal's orchids. (April 2023) - Bashyal, Reshu; Paudel, Kumar; Hinsley, Amy; Phelps, Jacob
Abstract: Governing wildlife resources is a global challenge, with illegal domestic and international trade emerging as a leading threat to biodiversity. This has prompted a range of international conservation commitments and domestic legislation, including protected species lists and legislation associated with the Convention on International Trade in Endangered Species of Wild Fauna and Flora (CITES). Despite their importance, heavy focus on national-level legislation potentially belies the complex networks of sub-national legislation that often inform on-the-ground wildlife management decisions. We highlight the need for a detailed understanding of sub-national legislation in order to meaningfully understand legal and illegal wildlife trade. We demonstrate this using the example of orchids – representing >70 % of all CITES-listed species – and focus on Nepal, a wildlife trade hotspot. We describe the available evidence on the country's overlapping legal and illegal orchid trade and provide a structured analysis of 55 pieces of domestic legislation that govern the country's orchid resources. It is likely that other countries and taxa face similar levels of complexity, and we propose an approach for more thorough and systematic evaluations of sub-national legislation – across areas of law, hierarchical levels of governance, and types of legislation.